The Global Financial Crisis: Impacts on SMEs and Government Responses - Wan, Yue (Université d'Ottawa / University of Ottawa, 2011)
This research examines the recent global financial crisis’ (GFC) impact on small- and medium-sized enterprises (SMEs) and analyses governments’ responses. According to most literature, SMEs already faced obstacles prior to the GFC, such as paying high taxes, overcoming low profitability, being affected by rising business costs, finding qualified labour, dealing with increasing competition, etc. The GFC has had serious repercussions for SMEs with respect to financing, markets, and liquidity. In order to explore in depth the governments’ responses, qualitative methods are employed to test the following three research questions: 1) To what extent did governments aim to assist SMEs to survive the GFC? What types of programs have been implemented to address new and existing obstacles? 2) Did governments apply appropriate strategic initiatives to realize their goals? If the initiatives could not achieve the governments’ original goals, what obstacles did they address? 3) Did governments tend to help SMEs more after the GFC? Did governments give up on disadvantaged firms or did they try to help them survive the crisis? Analysis revealed that, as a result of the GFC, governments developed programs aimed at new obstacles and at some of the existing ones. The aims did not differ materially for developed and less-developed economies. Financing and taxation programs tended to be designed to achieve their goals directly, where other programs tended to achieve them in a more indirect manner. Overall, government initiatives covered most of the serious obstacles faced by SMEs and government assistance programs aimed at SMEs tended to have been augmented in light of the GFC.
Keywords: SME; government program; public policy; global financial crisis; financing